Future Directions for Ureteral Stent Technology: From Bench to the Market. Issue 1 (17th November 2021) - Domingues, Beatriz; Pacheco, Margarida; de la Cruz, Julia E.; Carmagnola, Irene; Teixeira‐Santos, Rita; Laurenti, Marco; Can, Fusun; Bohinc, Klemen; Moutinho, Fabíola; Silva, Joana M.; Aroso, Ivo M.; Lima, Estêvão; et al.
Abstract: Ureteral stents are broadly used for the treatment of a wide range of pathologies, with different complexities and characteristics. Despite being efficient, the morbidity associated with stents, such as bacterial infection and pain, limits their therapeutic action and often represents an increase in healthcare costs. As no single solution fits all problems, there is still a need to improve these medical devices. Throughout this review, the most recent innovations are outlined and suggestions regarding future directions for ureteral stent technology are formulated with respect to materials, coatings, and designs of these devices. As highlighted here, during the process of passing these innovations to the growing market of ureteral stents, one of the biggest challenges is to increase the predictive value of the in vitro assays and, consequently, reduce the number of in vivo tests needed. Thus, recommendations concerning in vitro standard testing of these devices are provided, with focus on medium, flow conditions, and microbiological parameters. Additionally, the reader is also presented with insights about a crucial but rarely discussed topic, the bureaucratic part of the bench to market process, particularly the product certification legislation in Europe. Abstract : Research on ureteral stents is steadily improving. This review not only outlines the most promising advances, but also provides suggestions to enhance in vitro testing to facilitate their passage to the market. Additionally, the reader is also presented with insights about the crucial but rarely discussed topic of the bureaucratic journey that must be taken for technological leaps to happen.